Służby ratunkowe w Tatrach = Emergency services in the High Tatras - Joanna Siminska; Sara Przybylska; Anna Świątkowska; Iwona Domarecka; Waldemar Miszewski; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2017)
Siminska Joanna, Przybylska Sara, Świątkowska Anna, Domarecka Iwona, Miszewski Waldemar, Nowacka Krystyna, Hagner Wojciech. Służby ratunkowe w Tatrach = Emergency services in the High Tatras. Journal of Education, Health and Sport. 2016;6(11):404-411. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168477 http://ojs.ukw.edu.pl/index.php/johs/article/view/4016       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 25.11.2016.       Służby ratunkowe w Tatrach   Emergency services in the High Tatras   Joanna Siminska1, Sara Przybylska2, Anna Świątkowska1, Iwona Domarecka1, Waldemar Miszewski1, Krystyna Nowacka1, Wojciech Hagner1       1 Katedra i Klinika Rehabilitacji Collegium Medicum Uniwersytet Mikołaja Kopernika w Toruniu 2 Studenckie Koło Naukowe Dydaktyki ratownictwa i fizjoterapii  pourazowej Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu           Streszczenie               Co roku polskie Tatry odwiedza około 3 milionów osób. Tak duża liczba turystów wiąże się z nieuniknionym ryzykiem powstania wypadków. Na straży bezpieczeństwa gości Tatrzańskiego Parku Narodowego stają górscy ratownicy, zrzeszeni w Tatrzańskim Ochotniczym Pogotowiu Ratunkowym, a po stronie Słowacji Horskej Záchrannej Službie. Organizacje stanowią integralne części Państwowych Systemów Ratownictwa. Co roku ratownicy muszą interweniować kilka tysięcy razy, używając do tego specjalistycznego sprzętu oraz profesjonalnych pojazdów. System pogotowia górskiego w Polsce w dużej mierze opiera się na funduszach pochodzących z Ministerstwa Spraw Wewnętrznych, a także wpływów pozyskiwanych z biletów wstępu do Tatrzańskiego Parku Narodowego (15 procent). Dodatkowe pieniądze organizacja pozyskuje od sponsorów zewnętrznych. Horska Záchranna Služba jest w pełni finansowana z budżetu państwa, a zarządza nią Ministerstwo Spraw Wewnętrznych Republiki Słowackiej. Odpłatności za akcje ratownicze na Słowacji (poza śmigłowcem funkcjonującym tam na innych zasadach w ramach Pogotowia lotniczego) nigdy nie przekroczyły 8 procent budżetu.   Słowa kluczowe: służby ratunkowe, Tatry       Abstract               Every year, the Polish Tatras is visiting about 3 million people. So a large number of tourists involves the inevitable risk of the emergence of accidents. The security guard of the Tatras National Park are the mountain rescuers, members of the Tatras Rescue Alert Volunteer, and on the side of the Slovakia Mountain Rescue Service. Organizations constitute integral parts of the State Rescue Systems. Every year, the rescuers have to intervene a few thousand times, using special equipment and professional vehicles. The system of the mountain rescue service in Poland, largely based on the funds from the Ministry of Internal Affairs, as well as the proceeds derived from admission tickets to the Tatras National Park (15 percent). The extra money the organization acquires from external sponsors. Mountain Rescue Service is fully financed from the State budget, and managed by the Ministry of the Interior of the Slovak Republic. Extra payment for emergency actions.     Key words: emergency services, High Tatras